Potentially Inappropriate Drug Duplication in a Cohort of Older Adults with Dementia - Shanna C. Trenaman, BScH, BScPharm, MAHSR, ACPR, PhD; Susan K. Bowles, PharmD, MSc; Susan A. Kirkland, PhD; Melissa K. Andrew, MD, MPH, PhD (Elsevier, 2021)
ABSTRACT: Background: Concurrent use of 2 nonsteroidal anti-inflammatory drugs, selective serotonin reuptake inhibitors, loop diuretics, angiotensin-converting enzyme inhibitors, or anticoagulants is considered potentially inappropriate by Screening Tool of Older Persons' Prescriptions and Screening Tool to Alert to Right Treatment criteria. Objective: The objective was to examine drug duplication in a cohort of older adults with dementia. Methods: Cohort entry for Nova Scotia Seniors' Pharmacare Program beneficiaries was the date an International Classification of Diseases ninth edition or 10th edition code for dementia was recorded in accessed databases between March 1, 2005, and March 31, 2015. Medication dispensation and sociodemographic data were captured from the Nova Scotia Seniors' Pharmacare Program database between April 1, 2010, and March 31, 2015. Duplication was considered when 2 drugs from the same class were dispensed such that the supply in the patient's possession could overlap for more than 30 days. We reported number of cases of duplication and duration of overlap. Sex differences in drug duplication were assessed with bivariate logistic regression. Results: In the cohort of 28,953 Nova Scotia Seniors' Pharmacare Program beneficiaries with dementia, we documented concurrent use in 101 (1.7%) nonsteroidal anti-inflammatory drugs users (mean duration = 75.6 days), 95 (1.0%) selective serotonin reuptake inhibitors users (mean duration = 146.6 days), 5 (0.07%) loop diuretic users (mean duration = 530.6 days), 183 (2.0%) angiotensin-converting enzyme inhibitor users (mean duration = 123.9 days), and 160 (3.5%) anticoagulant users (mean duration = 63.6 days). Nonsteroidal anti-inflammatory drug pairs were most commonly celecoxib with naproxen or diclofenac. Selective serotonin reuptake inhibitors duplication was most commonly sertraline with citalopram. No sex differences in risk for drug duplication were identified. Conclusions: Drug duplication was identified in a cohort of older adults with dementia and is a feasible target for intervention. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)